Antioxidant Activity Test of The Ethyl Acetate Fraction of Tetanus Leaf (Leea aequata L.) Using The DPPH Method - Waruwu, Loice Desy Krisna Yanti; Bangar, Roy Indrianto; Kaban, Vera Estefania; Br Sembiring, Novitaria (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2025)
Degenerative diseases, such as diabetes, stroke, and cancer, are increasingly common in modern society, with free radicals as one of the main causes. Both natural and artificial sources of antioxidants are available. However, natural antioxidants are a better choice due to concerns over the negative effects of synthetic antioxidants. This study aims to evaluate the antioxidant activity of ethanol extract from titanus (leea aequata L.) leaves using DPPH (2,2-diphenyl-1-picrylhydrazyl) method. titanus leaves are known to contain secondary metabolites that have potential as antioxidants, including flavonoids and phenols. This type of research is an experimental method. The extraction process was carried out by maceration method using 96% ethanol, followed by fractionation using solvents with different polarities to obtain ethyl acetate fraction. The results showed that the ethyl acetate fraction showed the ability as a free radical antidote with an IC50 value of 11.309 ppm, which indicates significant antioxidant activity. These results indicate that titanus leaf extract has the potential to be used as a source of natural antioxidants in the prevention of degenerative diseases.